Konsep Darurat dalam Hukum Islam - Solikhin, Iin (Fakultas Syariah IAIN Purwokerto, 2008)
The important point in Islamic law is justice and punishment. This principal is the reference in deciding an Islamic law. The execution of daru>rah in Islamic law is natural because its priorities the ease and avoiding difficulties. Daru>rah has some meanings. Al-Jassa>s stated as the fear of the damage of soul and body. Daru>rah is something which is related to the big problems which need ease (mashaqqah).",